2023
DOI: 10.1136/bmj-2021-068033
|View full text |Cite
|
Sign up to set email alerts
|

Fracture risk reduction and safety by osteoporosis treatment compared with placebo or active comparator in postmenopausal women: systematic review, network meta-analysis, and meta-regression analysis of randomised clinical trials

Abstract: Objective To review the comparative effectiveness of osteoporosis treatments, including the bone anabolic agents, abaloparatide and romosozumab, on reducing the risk of fractures in postmenopausal women, and to characterise the effect of antiosteoporosis drug treatments on the risk of fractures according to baseline risk factors. Design Systematic review, network meta-analysis, and meta-regression analysis of randomised clinical trials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 205 publications
0
10
0
Order By: Relevance
“…A recent systematic review, network meta-analysis and meta-regression analysis of 69 randomized clinical trials, including more than 80,000 patients, concluded that bone anabolic treatments reduces the risk of fractures more than antiresorptive agents [ 35 ]. Furthermore, this analysis provided no clinical evidence for restricting the use of anabolic treatment to patients with a very high risk of fractures.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review, network meta-analysis and meta-regression analysis of 69 randomized clinical trials, including more than 80,000 patients, concluded that bone anabolic treatments reduces the risk of fractures more than antiresorptive agents [ 35 ]. Furthermore, this analysis provided no clinical evidence for restricting the use of anabolic treatment to patients with a very high risk of fractures.…”
Section: Resultsmentioning
confidence: 99%
“…8 In contrast, the FRAME trial did not suggest an increased incidence of MACEs associated with romosozumab (n=3589) in postmenopausal women with osteoporosis 32 A recent meta-analysis including the aforementioned randomized trials comparing romosozumab to placebo or other control treatments also showed no increased risk of serious adverse cardiovascular events or cardiovascular death associated with romosozumab. 33…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results also differ from a recent meta-analysis performed on > 80.000 patients that showed the benefit of osteoporosis treatment in postmenopausal women by reducing the refracture risk. This effect was mostly independent of baseline risk indicators [ 34 ]. This can be explained by microstructural studies which suggest that the predictive value of the bone mineral density decreases in the older population [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%